Sapote gum as a new biopolymer suitable emulsion stabilizer: Grapeseed oil ultrasonic emulsification - Arce-Rios, Katherin Lloy (2025)
Sapote gum (SG) is a new biopolymer with promissory functional properties. This study aimed to determine if SG is a suitable emulsifier for obtaining stable grape seed oil (GSO) emulsions. In the first stage, coarse emulsion concentrations of SG and grapeseed oil - GSO were evaluated, applying the Central Composite Rotational Design (0.59% to 3.41% of SG and 12.93% to 27.07% GSO). For the second stage, using a Centered Face Design – CFD, the resulting emulsion was sonicated at 90, 270, and 450 Watts at 5, 10, and 15 min. Finally, a validation was made. Emulsions were evaluated through microstructure, droplet size, kinetic stability, heat stress, and rheology. Micrographs of the first-stage emulsions showed droplets up to 3.8 μm diameter and a creaming index between 0.00% and 28.39% after 24 h. Optimization indicates that the higher the concentration of gum (3.5%) and GSO (25%), the more kinetically stable emulsions are produced. Ultrasonic emulsions showed no significant difference in droplet size and kinetic stability before 14 days of rest. Ultrasonic validation was made at 450 W for 6 min, resulting in emulsions stable for 20 days and with rheological characteristics interesting for food or cosmetic industries.